Adherence to diabetes mellitus care at three levels of health care - Jackline Duran Souza; Marcelo Henrique Barbosa Baptista; Danielle dos Santos Gomides; Ana Emilia Pace (Universidade Federal do Rio de Janeiro, 2017)
ABSTRACT Objective: To evaluate adherence to self-care among people with diabetes mellitus cared for at the three levels of health care. Method: Quantitative, descriptive, cross-sectional study addressing a sample of 143 people from a city in the interior of São Paulo, Brazil from primary (45), secondary (48) and tertiary (50) units. Adherence to self-care was assessed using the "The Summary of Diabetes Self-Care Activities Measure" and "Measurement of Treatment Adherence". Results: Adherence to exercises, blood glucose monitoring, shoe inspection, and the use of insulin differed between units; better results were obtained for those in tertiary care. Conclusion: The results indicate a need for greater investment in the initial phase of treatment to improve self-care adherence. Implications for practice: The study enabled identifying the profile of individuals in terms of self-care adherence and supporting the planning of nursing interventions in diabetes mellitus.